Internal Audit Function and Financial Performance : A Case Study of Centenary Bank Mukono Branch - Lillian Bangi (Uganda Christian University, 2023)
The study was carried out in Centenary Bank, Mukono branch. It was to examine the contribution of internal audit function and financial performance .The study was limited to the three objectives namely; to examine the relationship between quality of audit and financial performance in the study context, to assess the effect of internal audit function on financial performance of the study context and to examine the relationship between compliance and regulatory requirement and financial performance in the study context. The study used a case study research design. Study population included Management, Accountants and Operational employees totaling to twenty four respondents, all these were purposively selected. Data was analyzed quantitatively. The study findings revealed that authorization and approval, segregation of duties, routine and automatic checks, competence of staff, safe guarding of assets and integrity are major internal control function of the study context. It further revealed that the provision of value for money, financial transparency, adequate and timely service delivery, proper financial recording of accounts and management, proper financial accountability; measuring, evaluation of competence and efficient performance are major effects of internal audit function on financial performance in Centenary Bank, Mukono branch. It also revealed that proper financial accountability, value for money, high level of service delivery, promoting transparency and accountability, adequate timely service delivery, efficiency and proper utilization of department resources has been achieved due to internal audit function in Centenary Bank, Mukono branch. The study came up with recommendations to policy makers and financial institutions and also recommend further studies on the effect of internal audit function and financial performance.
This is a dissertation.